Promoting Plant Growth by ACC Deaminase Enzymes Producing Bacterial Endophytes under Biotic Stress Conditions - Mir, Mohammad Yaseen; Karabulut, Fadime (Apple Academic Press, 2024)
Environments in which plants are exposed to phytopathogens grow under biotic stress, and it modulates ethylene (ET) and is used as a signaling molecule in stress tolerance mechanismsIn the presence of these stress conditions, plants can induce higher levels of ET than their threshold values, resulting in reduced plant growth and crop productivityIn this context, bacterial endophytes play an important role in managing soil and plant health, as well as supporting plant growth under biotic stress conditions. Most endophytic bacteria appear to possess the enzyme aminocyclopropane- 1-carboxylic acid (ACC) deaminase, which enhances the growth of the host plantACC-deaminase is involved in regulating ET levels in plant developmentThese bacterial endophytes effectively degrade ACC-deaminase and simultaneously stimulate plant growth (such as increasing root length and plant biomass) at low ET levels and under stressful conditionsAdditionally, these bacteria play a crucial role in regulating plant physiology through the production of plant growth regulatorsEndophytes also act as microorganisms with beneficial mechanisms of action that increase crop yields, prevent, or even eliminate infections and pathogensThe goal of the researchers should be to uncover beneficial bacteria-plant interactions and manage this partnershipTo achieve this, the molecular interaction between plants and endophyte bacteria should be better demonstrated for the production of endophyte bacteriaIn the coming years, with increased awareness among manufacturers, more efficient products will be obtained under biotic stress conditions. © 2025 by Apple Academic Press, Inc.
Keywords: ACC deaminase enzyme; Bacterial endophytes; Biotic stress; Biotic stress tolerance; Plant physiology; Rhizobial infection; Stress reactions